Stability of the Cylindrical Panel. Experimental Investigations and Numerical Analysis - Marcinowski, J.; Antoniak, D. (Engineering Transactions, 1994)
The steel shallow cylindrical shell subjected to the action of a concentrated force applied at its center is the subject of the experimental test and-numerical analysis. Both investigations were performed within the large deformation range. At the same time strains and stresses remained small enough to ensure purely elastic material changes within the shell. Special attention was focussed on the stability phenomena. The fundamental equilibrium paths with all critical points as well as the postbuckling path were determined numerically. This solution was compared with the equilibrium path obtained in the experiment. Satisfactory agreement of the obtained solutions confirmed the correctness and versatility of the program used in the numerical analysis. The conclusions drawn from the comparative analysis performed are presented in the paper.